Relationship between Landuse Type and Temperature in Tanjong Malim, Perak - Ibrahim, Hairy; Hashim, Mohmadisa; Nayan, Nasir; Omar Baki, Mohd Hafiz; Che Ngah, Mohamad Suhaily Yusri (Journal of Techno-Social, 2010)
The purpose of this study is to identify whether there is a relationship between land use type and temperature in Tanjong Malim, Perak. Various analysis methodology have been examined to produce the relationship answer. One is correlation coefficient analysis. Beside that, GIS application is also used to produce temperature map. From the analysis done, they are several temperature variations detected in Tanjong Malim. Pearson correlation analysis is tested in three different situations namely average temperature for morning, noon and afternoon. Average temperature in the morning showed that the agriculture land use are with negative correlation value (r = -0.381), mean while average temperature in the noon showed the negative value for business and commercial land use (r = -0.541), and the average temperature for afternoon showed the positive value with residential area (r = 0.454). The negative value produced showed the flow of relationship is established within land use and temperature. The relationship between land use and temperature in Tanjong Malim is only at the level of medium high or very weak. There is no strong relationship between land use and temperature in Tanjong Malim. Urbanization is still low in this area and this does not affect the change and temperature variance in Tanjong Malim.